The impact of immunotherapy on the prognosis of small cell carcinoma of the esophagus: a propensity score-matched analysis of a retrospective study - Wang, Bing; Liu, Tianxing; Yang, Zhe; Zhu, Hui; Zhou, Fengge; Li, Li; Feng, Bin; Jing, Wang (Frontiers in Immunology, 2025)
ObjectiveSmall cell carcinoma of the esophagus (SCCE) is a rare neuroendocrine malignancy with no standardized treatment regimen. This study aims to evaluate the impact of immunotherapy on the prognostic survival outcomes of patients with SCCE.MethodsA retrospective analysis was conducted on 83 SCCE patients treated at the Provincial Hospital of Shandong First Medical University and the Cancer Hospital of Shandong First Medical University from January 2020 to June 2024. Propensity score matching (PSM) was applied to minimize potential biases between patients who received combination immunotherapy and those who did not. Survival outcomes, including overall survival (OS) and progression-free survival (PFS), were assessed using the Kaplan-Meier method, while univariate and multivariate analyses were performed using the Cox proportional hazards model.ResultsAmong the 83 patients included, 33 received combination immunotherapy and 50 did not. Prior to PSM, clinicopathological comparisons revealed that tumor size was significantly larger in the non-immunotherapy group (P = 0.032), and the immunotherapy group had more advanced N stages (P = 0.015). After 1:1 PSM, 20 matched pairs were analyzed. The immunotherapy group demonstrated a significantly longer OS compared to the non-immunotherapy group (22 months vs. 13 months, P = 0.0165), though PFS differences were not statistically significant (9 months vs. 7 months, P > 0.05). Univariate and multivariate analyses identified treatment methods (P=0.039) as independent prognostic factors for OS. Survival rate analysis showed that patients in the immunotherapy group achieved superior six-month (97.0% vs. 83.7%), one-year (78.9% vs. 56.5%), and two-year (22.1% vs. 10.4%) survival rates compared to the non-immunotherapy group.ConclusionsThis study demonstrates that combination immunotherapy significantly improves overall survival in SCCE patients and represents an effective treatment strategy for this rare malignancy.